2022
DOI: 10.3390/biomedicines10112987
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine Reduces L-Type Calcium Current without Major Changes in Repolarization of Canine and Human Purkinje and Ventricular Tissue

Abstract: Vagal nerve stimulation (VNS) holds a strong basis as a potentially effective treatment modality for chronic heart failure, which explains why a multicenter VNS study in heart failure with reduced ejection fraction is ongoing. However, more detailed information is required on the effect of acetylcholine (ACh) on repolarization in Purkinje and ventricular cardiac preparations to identify the advantages, risks, and underlying cellular mechanisms of VNS. Here, we studied the effect of ACh on the action potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 79 publications
3
4
0
Order By: Relevance
“…The absence of AP repolarization changes is in line with the work of Veerman et al [22] and Li et al [23], who found that CCh did not lead to major alterations in APD in RA-treated hiPSC-CMs, except when I K,ACh is largely increased by a GNB5 variant [32,33]. In contrast, muscarinic receptor activation in human atrial tissue [53,54] and freshly isolated human isolated cardiomyocytes [55] results in an AP shortening. The exact reason for this discrepancy is unknown, but it may be related to the still somewhat immature electrophysiological properties of hiPSC-CMs [56] and potential differences in I K,ACh density between hiPSC-CMs (Figure 2) and human atrial cells [55].…”
Section: Discussionsupporting
confidence: 85%
“…The absence of AP repolarization changes is in line with the work of Veerman et al [22] and Li et al [23], who found that CCh did not lead to major alterations in APD in RA-treated hiPSC-CMs, except when I K,ACh is largely increased by a GNB5 variant [32,33]. In contrast, muscarinic receptor activation in human atrial tissue [53,54] and freshly isolated human isolated cardiomyocytes [55] results in an AP shortening. The exact reason for this discrepancy is unknown, but it may be related to the still somewhat immature electrophysiological properties of hiPSC-CMs [56] and potential differences in I K,ACh density between hiPSC-CMs (Figure 2) and human atrial cells [55].…”
Section: Discussionsupporting
confidence: 85%
“…According to Eq. 1 , the injected I K1 exhibits a peak outward amplitude of 2 pA/pF, as routinely used in our laboratory (see, e.g., Veerman et al, 2016 ; Hilderink et al, 2020 ; Knottnerus et al, 2020 ; Verkerk et al, 2021a ; Koncz et al, 2022 ; Verkerk et al, 2022 ). Such I K1 amplitude results in quiescent hiPSC-CMs with a resting membrane potential near −80 mV.…”
Section: Methodsmentioning
confidence: 89%
“…These days, the dynamic clamp technique is routinely used in our patch-clamp laboratory. We have published several papers on the dynamic clamp technique per se ( Wilders, 2006 ; Berecki et al, 2014 ; Verkerk et al, 2017 ; Verkerk and Wilders, 2021 ) as well as on studies in which the dynamic clamp technique was used as a tool in patch-clamp experiments on cultured or freshly isolated atrial cardiomyocytes ( Majumder et al, 2020 ; Verkerk et al, 2021b ) or on hiPSC-CMs ( Meijer van Putten et al, 2015 ; Veerman et al, 2016 ; Portero et al, 2017 ; Veerman et al, 2017 ; Eroglu et al, 2020 ; Hilderink et al, 2020 ; Knottnerus et al, 2020 ; Verkerk et al, 2021a ; Eroglu et al, 2021 ; Marchal et al, 2021 ; Koncz et al, 2022 ; Portero et al, 2022 ; Verkerk et al, 2022 ; Nasilli et al, 2023 ) to supply these cells with a synthetic I K1 during AP measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The cells were then detached from the surface by pipetting, the enzyme solution was diluted with addition of RPMI/B27− medium and the cells in suspension were collected by centrifugation. The cell pellet was further dissociated in presence of Liberase TM Research Grade (Roche/Merck) as previously reported 40 . The hiPSC-CMs, seeded on Matrigel Matrix-coated cover glasses (VWR International GmbH) in RPMI 1640/B27− medium, were analysed 8-10 days after dissociation.…”
Section: Electrophysiology Patch Clamp Analysis Preparation Of Hipsc-...mentioning
confidence: 99%